Local residents attitudes towards the impact of tourism development in Cape Verde - Cañizares,Sandra María Sánchez (2014)
The attitudes and perceptions of local communities or residents are of special interest when examining and managing the economic, socio-cultural and environmental aspects of tourism development in a given area. In this paper, we analyse the perceptions and attitudes of residents in an emerging tourist destination: the island country of Cape Verde (Africa). A survey and multivariate analysis is used for the analysis. More specifically, we focus on the island of São Vicente, an enclave that has remained relatively isolated from foreign tourism until fairly recently, and which is currently experiencing a tourism boom that is altering the way of life of local residents. The results reveal that, in general terms, the local community perceives that tourism brings economic opportunities - especially for a population whose traditional fate was to emigrate - and has other positive impacts such as increased investments in infrastructures and higher quality hospitality and retail establishments.